2018
DOI: 10.26719/2018.24.6.512
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for overweight and obesity among adolescents in Morocco

Abstract: This study provides useful findings that could be elaborated on and expanded in studies on overweight and obesity among adolescents in Morocco.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 34 publications
5
16
2
3
Order By: Relevance
“…Table (1) revealed that 24 (40%) of the patients with obesity with sleep duration more than ten hours and 14 (23.4%) of healthy control with sleep duration more than ten hours, and this result suggested increased obesity with increased sleep duration, but these results indicated no significant difference in the frequency distribution of patients and control subjects according to sleep duration (P = 0.138). The results of present study agree with results of El-Kabbaoui et al, (14) . (2018), which indicated 78 (38.6%) of patients has had more than ten hours sleep duration and these result indicate no significant association between the daily duration of sleep and risk for overweight or obesity (P = 0.75).We found a statistically significant relation between family income and risk of obesity, where the obesity increasing with increasing family income 30 (50%) of patients have had high average family income.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Table (1) revealed that 24 (40%) of the patients with obesity with sleep duration more than ten hours and 14 (23.4%) of healthy control with sleep duration more than ten hours, and this result suggested increased obesity with increased sleep duration, but these results indicated no significant difference in the frequency distribution of patients and control subjects according to sleep duration (P = 0.138). The results of present study agree with results of El-Kabbaoui et al, (14) . (2018), which indicated 78 (38.6%) of patients has had more than ten hours sleep duration and these result indicate no significant association between the daily duration of sleep and risk for overweight or obesity (P = 0.75).We found a statistically significant relation between family income and risk of obesity, where the obesity increasing with increasing family income 30 (50%) of patients have had high average family income.…”
Section: Discussionsupporting
confidence: 93%
“…Watching television may reduce energy expenditure by replacing physical activity and also increase snacking, which is further encouraged by advertisements for energy-dense foods (17) . Our results agree with results of El-Kabbaoui et al, (14) , which indicated non-significant correlation between watching television daily for ≥ 4 h with the risk of childhood for obesity (p= 0.32). The present results found inverse statistically significant relation between the prevalence of obesity and physical activity (P= 0.003), where the frequency distribution of childhood obesity patients according to physical activity was as following : 26 (43.3 %) patients having physical activity and 34 (56.7 %) don't having physical activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overweight and obesity among schoolchildren and adolescents are a major public health challenge facing societies in many parts of the world [3,4]. Children and adolescents suffer from overweight and obesity in both developed and developing countries [5], and the international prevalence has risen within the period 1975-2016 from 4% to >18% in adolescents of both genders [6]. Globally, 340 million individuals aged 5-19 years were overweight in 2016 [6] and nearly 13 million aged 2-19 years were obese [7].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a common global health problem caused by different factors such as endocrine disorder, metabolic syndrome, improper diet, drugs, or heredity [1,2]. It increases the risk of many chronic illnesses, including but not limited to hypertension, type 2 diabetes mellitus, cardiovascular diseases, musculoskeletal disorders, sleep apnea, and certain types of cancer [2-5].…”
Section: Introductionmentioning
confidence: 99%